The Rise of New Brokerages and the Restructuring of Real Estate Value Chain - Ba, Shusong (Springer Singapore, 2018)
This book elaborates on the six pillars of a healthy and standardized real-estate brokerage industry: the generation, distribution and matching of information; the transaction system; circulation finance; mobile Internet; the supervision system; and professional brokers. With each of these pillars playing a role, they also mutually interact to constitute an integrated framework that regulates the brokerage industry. Presenting practicable, extensive and cutting-edge research that encompasses various areas of the industry and detailed case studies from around the globe, the book provides a number of suggestions that have already been adopted and have begun to take effect. It also explores the frontiers of the real-estate brokerage industry - the incorporation of the internet, the blurred boundary between online and offline service where brokerages are moving online, client acquisition is via the internet, and benchmark companies are focusing more on their trading service capacity, each building their own controllable trading environment.